Response of Cowpea (Vigna unguiculata L.) Varieties to Different Sowing Dates on Growth, Yield and Economics - SUTAR, V. K.; CHAVAN, L. S.; GAME , V. N.; KHETRE, O. S. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Cowpea (Vigna unguiculata L.) is the most important legume in the world. It is an important source of dietary protein in developing countries of Asia and Africa. It is used as fodder, vegetable pulse and green manure crop. The economic importance of cowpea is difficult to ascertain as the production statistics are no longer kept separate from those of other pulses. Summer cowpea is grown as catch crop in Konkan region in the areas where irrigation facilities are available. Proper sowing time is the most important non-monetory factor in crop production, which affects the crop growth, yield and quality to great extent. Time of sowing plays an important role to fully exploit all available resources for growth as it provides optimum growing conditions such as temperature, light, humidity and rainfall. A small change in sowing time leads to significant changes in performance of crop.